A Rising E-Channel Tide Lifts All Boats? The Impact of Manufacturer Multichannel Encroachment on Traditional Selling and Leasing - Wei Yan; Youwei Li; Ying Wu; Mark Palmer (Discrete Dynamics in Nature and Society)
Organizing and managing channels of distribution is an important marketing task. Due to the emergence of electronic commerce on the Internet, e-channel distribution systems have been adopted by many manufacturers. However, academic and anecdotal evidence both point to the pressures arising from this new e-channel manufacturing environment. Question marks therefore remain on how the addition of this e-channel affects the traditional marketing strategies of leasing and selling. We set up several two-period dual-channel models in which a manufacturer sells a durable product through both a manufacturer-owned e-channel and an independent reseller (leaser) who adopts selling (leasing) to consumers. Our main results indicate that, direct selling cost aside, product durability plays an important role in shaping the strategies of all members. With either marketing strategy, the additional expansion of an e-channel territory may secure Pareto gains, in which all members benefit.